Budaya Organisasi, Berbagi Pengetahuan Dan Kinerja Organisasi - Zulmaswan .; Nurliana .; Susandri . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The research was conducted at all junior high schools in Kuantan Tengah subdistrict with the aim of testing the role of knowledge sharing in mediating the influence of organizational culture on organizational performance. The population of this study was 197 people. Based on this population size, in accordance with the Krejcie and Morgan (1970) table, the sample size for this study was 132 people. The sampling method used in this research is Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a 1-5 point Likert scale. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This research found that organizational culture has a significant positive effect on organizational performance, organizational culture has a significant positive effect on the dissemination of knowledge, knowledge sharing has a significant positive effect on organizational performance, knowledge sharing mediates the influence of organizational culture on organizational performance.